Cat scratch disease causing encephalitis. Issue 3 (2nd July 2020) - Fan, Jerry; Ali, Hameed
Abstract: Cat scratch disease is often a benign infection caused by Bartonella henselae, which is transmitted from scratches or bites from kittens. Presentations can vary from localized lymphadenopathy to neurologic manifestations. We present a case of a 22-year-old man with a 3-week history of an enlarged inguinal lymph node who presented with status epilepticus.